Prevalence of celiac disease in Brazilian children of short stature - M.S. Queiroz; M. Nery; E.L. Cançado; D. Gianella-Neto; B. Liberman (Brazilian Journal of Medical and Biological Research, 2004)
The aim of the present study was to determine the prevalence of celiac disease in children of short stature and to assess whether some of the routine laboratory examinations performed to determine the cause of short stature could suggest the presence of celiac disease. A total of 106 children of short stature and no gastrointestinal symptoms were studied. An extensive endocrine work-up had been negative for all of them and an additional investigation was performed by measuring the concentration of antiendomysial antibody. Patients who were positive for antiendomysial antibody ( > or = 1:10) or who exhibited IgA deficiency (less than 5 mg/dl) were referred for an endoscopic intestinal biopsy. We detected a pathological titer of antiendomysial IgA in six of these patients. Five of them showed histological abnormalities compatible with celiac disease and one had normal histology and was considered to have potential celiac disease. The prevalence of celiac disease in the population studied was 4.7% (with another 0.9% of the subjects being considered to have potential celiac disease). The children with celiac disease did not differ in any of the parameters tested when compared to those without celiac disease, though they showed an improvement in growth velocity after treatment with a gluten-free diet. We conclude that it is important to test all children with short stature for celiac disease by measuring antiendomysial IgA.